2010
DOI: 10.1002/cncr.25100
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter analysis of lung cancer patients younger than 45 years in Shanghai

Abstract: BACKGROUND:The treatment, prognosis, and outcomes of young lung cancer patients have not been fully explored. In addition, there is a pressing need to characterize this subgroup of patients, because there is a trend of increasing incidence in younger patients from Europe and Japan. METHODS: Consecutive, nonselected young patients (<45 years old) with pathologically diagnosed lung cancer treated at 175 qualified hospitals in the greater Shanghai area were included in this analysis. Incidence, prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 30 publications
3
61
1
Order By: Relevance
“…It is rare in young patients. Many studies suggested that the disease may represent a specific entity in these young subjects or, at least, is associated with specific characteristics: female over-representation [7][8][9][10][11][12][13][14][15][16], predominance of adenocarcinoma [7,[9][10][11][12][13][14][16][17][18][19] and advanced stage at diagnosis [8, 9, 11-13, 15, 16, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rare in young patients. Many studies suggested that the disease may represent a specific entity in these young subjects or, at least, is associated with specific characteristics: female over-representation [7][8][9][10][11][12][13][14][15][16], predominance of adenocarcinoma [7,[9][10][11][12][13][14][16][17][18][19] and advanced stage at diagnosis [8, 9, 11-13, 15, 16, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concluded that young patients had a longer survival [10,12,13,[15][16][17][18], although the authors sometimes acknowledged that they received more aggressive treatment, others found a shorter survival [19], and many studies did not find any survival difference between young and older patients [9,14,[21][22][23][24]. However, these results cannot be compared because the cut-off used to define young patients varies from 40 to 50 years, and the populations included in these studies are heterogeneous, sometimes limited to non-small cell lung cancer (NSCLC) or adenocarcinoma or restricted to patients who underwent surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous papers focused on young NSCLC patients, each with varying definitions of "young" [5][6][7][8]. Some of these studies attempted to compare outcomes between younger and older NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Reports also show that adenocarcinomas are more frequent than squamous cell carcinomas and comprise the majority of tumors among young patients, never smokers, and female patients with lung cancer, respectively. [3][4][5] Cigarette smoking is the major risk factor for lung cancer in young people. The smoking rate among young patients with lung cancer is 45% to 97% in western countries.…”
Section: Discussionmentioning
confidence: 99%